ANALISIS PSIKOLOGI SASTRA TOKOH-TOKOH NOVEL BIOLA PASIR DARI MASA LALU KARYA D.K. SUMIRTA - Dewi Anggraeni, Ni Komang (Humanis; Volume 15. No.2. Mei 2016, 2016)
This study analyzes the novel Biola Pasir dari Masa Lalu by D.K. Sumirta by using a psychological approach to literature that focuses on the study of personality psychology and psychosexual. The theories used are the structural theory and the theory of psychology literature. Structural theory is used to analyze the intrinsic elements, while theory of psychology literature to assess aspects of personality and psychosexual figures Biola Pasir dari Masa Lalu. To analyze the personality aspect, personality psychology Sigmund Freud used that divides human personality into three psychological elements, id, ego, and superego. Furthermore, psychosexual theory presented by Hurlock.
Keywords: Novel, personality psychology, and psychosexual